Software de control de asistencia estudiantil para el colegio "29 de agosto" del recinto Mata de Cacao del cantón Babahoyo - Sánchez Ledesma, Fernando Esmeider (2019)
The computer system for the control of student attendance of the students of the school ‘‘August 29 ’’ will offer the authorities and teachers to keep an automated attendance record. After analyzing the deficiencies of the school, which was their attendance control, we decided to find a way to improve that lack by designing a computer system that could meet their needs. Once the system was designed, it was determined that it meets the needs requested by teachers and authorities, so it can be concluded that this technological proposal will achieve a positive result in the school `` August 29 '', because before they did not have a system that facilitates the processes of assistance control